Discrete Optimization: Theory, Algorithms, and Applications (MDPI - Multidisciplinary Digital Publishing Institute, 2024)
This Special Issue reprint from Mathematics presents, in addition to the Editorial, 18 research papers in the field of Discrete Optimization. The subjects addressed in this reprint cover a broad spectrum of subjects, e.g., graphs and networks, single- and two-machine scheduling, and goal programming.